Arduino-Based Controller for Sequence Development of Automated Manufacturing System - Khaleel, Shahad Sarmad; Salloom, Maher Yahya; Shammari, Ahmed M. (Al-Khwarizmi Engineering Journal, 2020)
It has become necessary to change from a traditional system to an automated system in production processes, because it has high advantages. The most important of them is improving and increasing production. But there is still a need to improve and develop the work of these systems. The objective of this work is to study time reduction by combining multiple sequences of operations into one process. To carry out this work, the pneumatic system is designed to decrease increase the time of the sequence that performs a pick and place process through optimizing the sequences based on the obstacle dimensions. Three axes are represented using pneumatic cylinders that move according to the sequence used. The system is implemented and controlled to carry an object from one position to another. The movement of the system is controlled using three linear potentiometers, which are connected to an analog input of the microcontroller to feed the value of the pneumatic rod distance. To achieve the best path of the product moving, it is necessary to compare among several sequences. . The results show the sequences that compared with the reference under fixed speed, such as sequence that has been developed by combining two axes, and then the system path time has been reduced in taking the product from one place to another. Therefore, some factories need to reduce the sequences and thus reduce the time to transfer the product.